Experimental investigation of plain- and flapped-wing tip vortices - Elsayed, Omer Ali; Asrar, Waqar; Omar, Ashraf A.; Kwon, Kijung; Jung, Hyejin (http://www.aiaa.org/IframeTwoColumn.aspx?id=4739, 2009)
Particle image velocimetry was used in a low-speed wind tunnel to investigate and characterize wing tip vortex structures. A rectangular wing of a subsonic wall interference model was used as a vortex generator in two different configurations: 1) plain wing and 2) flapped wing with the trailing-edge flap extended at 20 degrees. Vortex flow quantities and their dependence on angle of attack at Reynolds numbers of 32:8 103 and 43:8 103 were evaluated. Assessment of measured data reveals that the peak values of tangential velocities, vortex strength, and vorticities are directly proportional to the angle of attack. The vortex core radius value grows slowly as the angle of attack is increased. Both plain and flapped configurations showed similar trends. The peak tangential velocities and circulation almost doubled when the flapped configuration was used instead of the plain wing.